Respons Kailan (Brassica oleracea Var. Winsa Kaelan Sharp Leaf) Pada Konsentrasi Poc Dan Komposisi Media Tanam Yang Berbeda - Isti Khoiriyah; Etik Puji Handayani; Syafiuddin Syafiuddin (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2022)
Kailan (Brassica oleracea) is vegetable can grow on all types of soil, enjoyed by the community so it has good prospects to be developed in Indonesia. Good Cultivation technique the production of kailan. Therefore, the use of liquid organic fertilizer combination with the composition of planting media needs to be applied as both can increase the product of kailan that is organic so that the needs of healthy vegetables can be completed. The purpose of this study are determine the best concentration of liquid organic fertilizer for growth and yield of kailan vegetables, the best planting media for growth and yield of kailan vegetables, and the interaction between of liquid organic fertilizer application and media type of planting toward the growth of kailan vegetables. The results of this research that the concentration of liquid organic fertilizer has no significant effect on growth and yield of kailan, the composition of different planting media has no significant effect on growth and yield of kailan except on the large ratio of leaf (RLD) and wet weight on kailan plant. and there is no interaction between liquid organic fertilizer and plant media composition on growth and yield of kailan plants.